PENGARUH METODE COORPERATIVE LEARNING JIGSAW TERHADAP KEMAMPUAN MENARI SISWA DIKEGIATAN EKSTRAKURIKULER SENI TARI SMA SWASTA SULTAN AGUNG PEMATANGSIANTAR - Vina Ayu Lestari; Sitti Rahmah; Martozet Martozet (Gesture: Jurnal Seni Tari, 2018)
Abstract -This study discusses about the learning model of Coorperative Learning Jigsaw activities extracurricular art of dance. The location of this research was conducted at SMA Perguruan Sultan Agung Foundation Surabaya. 19 Pematangsintar, North Sumatra. The theory used in this research is the learning model of Coorperative Learning Jigsaw (Amri and Ahmadi) and Capability Of Learning (Nurwani). The result of the research based on the collected data, it can be seen that the extracurricular activity of dance art is very influential on the learning model of Coorperative Learning Jigsaw to the students' dancing ability. From the results of questionnaire (questionnaire) showed that 91.95% of students liked the learning model Coorperative Learning Jigsaw given by the teacher. The result of student's dancing ability is 78,59%. Thus it can be concluded that the learning model Coorperative Learning Jigsaw very influential on the ability to dance students who have done well with effective and efficient time for four weeks. This means that this activity is very positive effect on the ability to dance with the learning model given by the teacher. Keywords: Cooperative Learning Jigsaw, Extracurricular Art of Dance his study.